Revealing violations of macrorealism in flavor oscillations: Leggett-Garg inequalities and no-signaling-in-time conditions - Blasone Massimo; Illuminati Fabrizio; Petruzziello Luciano; Simonov Kyrylo; Smaldone Luca (EPJ Web of Conferences, 2024)
Abstract. We briefly review recent developments in the study of the quantum nature of flavor mixing; in particular, the attention will be devoted to neutrino and neutral meson oscillations. We employ Leggett-Garg type inequalities and no-signaling-in-time conditions to probe the intrinsic quantumness of such a physical manifestation, showing how the analysis is not affected by the wave-packet spreading (for neutrinos) and the intrinsic particle instability (for mesons).